Patient-Centered Care and Process Improvement: A Systematic Review of Impacts on Satisfaction Outcomes - Alduways, khaled Hassan Ali; Al Rukhami , Nader Mohammad; Alduways, Hadi Saleh Hadi; Al Shahi, Salem Mubarak Mohammed; Alduways , Ibrahim Musallam; Mansour, Ali Hassan Hadi AI; Belharith , Abdullah Saleh; Duways, Khalid Mohammed Hadi Al; Masoud , Nassar Hamad; ALagil, Ibrahim Hamad (Journal of Ecohumanism, 2024)
Patient-centered care (PCC) has emerged as a crucial approach in enhancing healthcare delivery, focusing on the needs and preferences of patients. This systematic review explores the impact of process improvement strategies on patient satisfaction outcomes within PCC frameworks. Databases including PubMed, Scopus, and Web of Science were searched for relevant studies published between 2016 and 2024, analyzing the effectiveness of process improvement interventions such as Lean, Six Sigma, and workflow optimization in various healthcare settings. Inclusion criteria focused on studies that specifically measured patient satisfaction as an outcome. The review found that process improvement initiatives positively influence patient satisfaction by streamlining care delivery, reducing wait times, and improving communication between healthcare providers and patients. However, variations in intervention types and healthcare settings highlight the need for context-specific applications. This review underscores the importance of integrating process improvement tools into PCC practices to achieve better satisfaction outcomes and improve overall care quality. Future research should focus on long-term effects and broader applications of these interventions in diverse healthcare environments.